Colour in the environment for older adults - Mgr. art. Monika Hencová; Prof. Ing. Veronika Kotradyová, PhD. (Architecture Papers of the Faculty of Architecture and Design STU, 2023)
Demographic changes, the growing number of people with disabilities, and the demands on architecture and design are posing new challenges for designers. The space in which older adults live should be safe, not only from a legal point of view but especially to facilitate their daily activities. Modern society prioritizes the integration of older adults into everyday life so that as people grow older, they are not forced to abandon their daily routines because of obstacles in the space. It is said that a person is not handicapped because of their illness, but because society fails to prepare conditions for them to be able to move and live without restrictions. Moving in space is a multisensory experience. People use most of their senses such as sight, hearing, smell, and touch in addition to moving their bodies. How we feel indoors depends on the indoor climate, lighting, surface colours, air quality, floor plan, and furniture layout. Studies show that the materials and colour of products have an impact on how we navigate a space, how we feel and, in some cases, they can even have healing effects. The aim of our study is to investigate the association between colours in the environment and the orientation of people, especially older adults, in the space they live in. Several studies, experiments, and observations of foreign researchers serve as the basis of the paper. The analysis of case studies proved that colours in the environment have a significant impact on orientation in space and can be an effective tool for spatial orientation and drawing attention to a particular place. In surveys that have been conducted with older adults, warm colour tones such as yellow, orange, and red are preferred over cold ones. Red tones are some of the most easily recognizable for older adults who suffer from loss of colour recognition. They have lower cognitive abilities as a result of aging. Therefore, the achromatic environment does not sufficiently stimulate their brain function, leading to longer reaction times. Colour and contrast indoors play a big role in the perception of space and can help in drawing attention to a particular place.